Islamic personal law and it’s realities in Albanian society in the absence of Islamic legislation / Klodjan Adriatik Zaimaj - Klodjan Adriatik , Zaimaj (2016)
The objective of this research is to shed light on the area of family law in Albanian society in light of the absence of Islamic laws and courts. This research attempts to achieve that by discussing marriage, divorce and inheritance and their respective rulings in Albanian family law and civil law. This research is important because it draws attention to the painful legal reality that Albanian Muslims live in these times by discussing their legal, familial and social situations and the related judicial and Shari’ah matters. This research relies upon a research methodology of gathering the literature related to this topic and an analytical methodology of analysing the academic material and finding solutions. Additionally, this research proposes solutions to the issues that arise due to the absence of Islamic laws. This research has come to a number of conclusions and recommendations. The most important ones include that the Albanian Family Code is very different from the Islamic Shari’ah and is manmade law. Also, the Albanian government needs to prepare for the Muslims that which will protect their rights in issues related to family law by recognizing Islam as its religion in the Constitution and legislating based on the Shari’ah. Additionally, this can be done by establishing Shari’ah courts that judge using the Shari’ah or by establishing judicial bodies within the existing courts that will judge using the Shari’ah. This research also finds it necessary to establish Islamic arbitration centres and organizations recognized by the government that fully comprehend the Shari’ah and Albanian law to resolve the issues of the Albanian Muslims in family matters Lastly, the Islamic Affairs Committee needs to expand itsauthority to include supervising the application of the Islamic rulings in relation to family matters and to be the final authority in making judgements in family law cases so that it can document marriage contracts, divorce, and inheritance because it is the official body that represents Albanian Muslims. The researcher interviewed some relevant individuals including the Head of the Islamic Affairs Committee to propose solutions similar to these; he determined that the Committee is not seeking to achieve that because the society, according to them, is not ready for that and because the government is secular so the Islamic Affairs Committee cannot take on these authorities in accordance with the vision of the Head of the Committee.